Perancangan Simulasi Pendaftaran Mahasiswa Baru UIN Sultha Thaha Saifuddin Jambi menggunakan Animasi Berbasis Multimedia - Ahmad Nafis; M. Yusuf; Fatima Felawati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Currently at UIN Sulthan Thaha Saifuddin Jambi, there is an outreach to find new students for high school and equivalent schools which is carried out every year. The socialization process explains the steps for registering new students. In the future, it is hoped that many prospective students will register to become new students. UIN Sulthan Thaha Saifuddin Jambi. In designing this simulation using the MDLC (Multimedia Development Life Cycle) method, the stages in the MDLC method can make the simulation design in the form of animation complete. This research method provides information using instruments with a qualitative approach. This method collects data provided or obtained from sources, both written and verbal. A qualitative approach is carried out by interviewing sources directly, making direct observations from the field. The beta test results show that the animated simulation video for new student admissions at UIN Sulthan Thaha Saifuddin Jambi obtained an average percentage of 87%. The highest percentage score was 93% for the assessment of the first question regarding sound quality and the fourth question regarding whether the animated simulation video could be played well.